Agrobacterium Protocols
DOI: 10.1385/1-59745-130-4:43
|View full text |Cite
|
Sign up to set email alerts
|

Three Methods for the Introduction of Foreign DNA into <i>Agrobacterium</i>

Abstract: The genetic manipulation of Agrobacterium tumefaciens is used to facilitate studies of bacterial gene functions or as a first step in introducing genetic material into transformable plant cells through the use of T-DNA binary vectors. Three methods are commonly used. Transformation with purified plasmid can be done with either electroporation or a simple freeze/thaw transformation method. Alternatively, a mobilizable plasmid can be placed into Agrobacterium using the triparental mating method. Here we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
0
5

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(135 citation statements)
references
References 11 publications
0
130
0
5
Order By: Relevance
“…Bacterial DNA transformation was conducted by using chemically competent E. coli DH5a (Invitrogen), electroporation of E. coli Rosetta (DE3), or through freeze/thaw transformation of CaCl 2 -competent A. tumefaciens (29). N. tabacum (variety Turk), and A. thaliana plants were grown in a controlled growth chamber at 24°C at 16-h light/8-h dark photoperiod before infiltrations and switched to 24-h light after infiltrations.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial DNA transformation was conducted by using chemically competent E. coli DH5a (Invitrogen), electroporation of E. coli Rosetta (DE3), or through freeze/thaw transformation of CaCl 2 -competent A. tumefaciens (29). N. tabacum (variety Turk), and A. thaliana plants were grown in a controlled growth chamber at 24°C at 16-h light/8-h dark photoperiod before infiltrations and switched to 24-h light after infiltrations.…”
Section: Methodsmentioning
confidence: 99%
“…After incubation at 37°C for 1 hour, 50-μl aliquots were plated onto LB agar supplemented with rifampicin and other antibiotics that were selective for recipient cells that had acquired incoming plasmid. Electroporation was performed as described by Wise et al (2006) using a Cell-Porator (BRL, Gaithersburg U.S.A) with Bio-Rad Pulser cubettes ( 1 mm electrode gap ) under the following conditions: voltage, 300 V; capacitance, 330 μF; impedance, low ohms; charge rate, fast; voltage boost resistance, 4 K. After electroporation the cells were immediately re-suspended in 1 ml of SOC medium, and incubated at 28°C with gentle shaking for 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…Following a recovery, this protocol yielded a surprisingly high transformation efficiency of~10 4 cfu. Low-temperature transformations in bacteria have been previously reported, originally by Dityatkin et al in 1972 [18]; however, they have only found widespread use in Agrobacterium tumefaciens transformations [19][20][21], and examples in E. coli are rare. This is most likely due to relatively low transformation efficiencies compared to other methods and the overall prevalence of both electroporation and heat shock protocols.…”
Section: E V E L O P M E N T Of M I C Row a V E -M E D I A T E D Bamentioning
confidence: 99%